A miniaturized screen for inhibitors of Jumonji histone demethylases. - Sakurai, M; Rose, N; Schultz, L; Quinn, A; Jadhav, A; Ng, S; Oppermann, U; Schofield, C; Simeonov, A (2010)
2-Oxoglutarate- and Fe(ii)-dependent oxygenases are a major class of N(epsilon)-methyl lysine demethylases that are involved in epigenetic regulation. Assays suitable for implementation in a high-throughput manner have been lacking for these enzymes. Here, we describe the design and implementation of a robust and miniaturized high-throughput kinetic assay for inhibitors of JMJD2E using a formaldehyde dehydrogenase-coupled reaction with real-time fluorescence detection. Reactant compatibility studies resulted in simplification of the assay scheme to the mixing of two reagent solutions, both of which were stable overnight. The assay was miniaturized to a 4 microL volume in 1536-well format and was used to screen the library of pharmacologically active compounds (LOPAC(1280)). Inhibitors identified by the screen were further characterized in secondary assays including FDH counterscreen and demethylation assays that monitored demethylation by MALDI-TOF MS. The assay developed here will enable the screening of large compound libraries against the Jumonji demethylases in a robust and automated fashion.